Conflict, community, and COVID-19: response and implications in Ethiopia - Martin Plymoth; Yidnekachew G. Mogessie; Israa Mohammed; Dawit Mengesha; Mandy Wang; Shuaibu Saidu Musa; Bezawit Kassahun Bekele; Heaven Yeshaneh Tatere; Mohamed Babiker Musa; Don Eliseo Lucero-Prisno, III (AOSIS, 2022)
Community transmission of COVID-19 is currently on the rise in Ethiopia, while availability of diagnostic and treatment services remains limited. Impaired access to essential services is affected by the pandemic's strain on the health system, and as a consequence of the country's public health response. The ongoing conflict in the Tigray Region provides another obstacle to accessing and providing care for the local population; and has displaced large numbers of people both within and outside the country. In this commentary we discuss the impact of the conflict on essential services and argue that a coordinated holistic response is essential to mitigate both short and long-term consequences of the conflict, including increased COVID-19 transmission, acute malnutrition, disruption of education services, displacement of people, and food insecurities. We highlight the important role of community engagement in prevention and early detection of these challenges, and the need for comprehensive interventions in the region.